Produksi, Karakterisasi, dan Isolasi Lipase dari Aspergillus niger menggunakan Minyak Goreng Sawit sebagai Induser - Sri Wahyu Murni; Siti Diyar Kholisoh; Tanti D.L.; Petrissia E.M. (Eksergi, 2015)
The objective of the research was to produce, isolate and characterise lipase from Aspergillus niger, and therefore inducted it by using palm oil. The lipase enzyme was produced through a batch fermentation process in a 1.4 liters-fermentor. Fermentation was carried out at room temperature, initial pH of 7, the stirring speed of 250 rpm, aeration rate of 1 vvm, and inducer concentration of 3%-m/v palm oil/ml. Enzymes was characterised at several temperature and pH variations. The lipase showed the optimum performance at pH of 7 and temperature of 30 °C with the activity of 1.5 U / ml. Isolation of lipase yielded a 4-times-increase in its activity by using 90% ammonium sulfate.